2005
DOI: 10.1037/0033-295x.112.2.347
|View full text |Cite
|
Sign up to set email alerts
|

From the Lexicon to Expectations About Kinds: A Role for Associative Learning.

Abstract: In the novel noun generalization task, 2 1/2-year-old children display generalized expectations about how solid and nonsolid things are named, extending names for never-before-encountered solids by shape and for never-before-encountered nonsolids by material. This distinction between solids and nonsolids has been interpreted in terms of an ontological distinction between objects and substances. Nine simulations and behavioral experiments tested the hypothesis that these expectations arise from the correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
286
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(299 citation statements)
references
References 99 publications
(186 reference statements)
13
286
0
Order By: Relevance
“…The implication of this prediction was that visual similarity of nonsolid items of the same material can support generalization, but vocabulary exposure is needed for shape-based generalization to emerge. Colunga and Smith (2005) administered the noun generalization task to a sample of younger children and found empirical support for this prediction: Children who had not yet learned many words could generalize the names of nonsolid items by material.…”
Section: Novel Developmental Predictionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The implication of this prediction was that visual similarity of nonsolid items of the same material can support generalization, but vocabulary exposure is needed for shape-based generalization to emerge. Colunga and Smith (2005) administered the noun generalization task to a sample of younger children and found empirical support for this prediction: Children who had not yet learned many words could generalize the names of nonsolid items by material.…”
Section: Novel Developmental Predictionsmentioning
confidence: 99%
“…For example, Rakison and Lupyan's (2008) simulation showed that long-term experience with objects in the real world can constrain the feature correlations that children can learn in the lab. Similarly, Colunga and Smith (2005) have shown that linguistic experience, as evidenced by vocabulary size, can constrain the manner in which children generalize novel nouns such that they learn to use different properties to generalize about different types of objects. Both simulations highlight the emergence of complex constraints on behavior from domain-general associative learning as long-term accumulated weights affect the moment-to-moment behaviors.…”
Section: Creation Of a Unifying Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of empirical and theoretical literature on word acquisition exists (Colunga and Smith, 2005;Regier et al, 2005;Garagnani et al, 2008;Cummings et al, 2009;Frank et al, 2009;Mayor and Plunkett, 2010). Many proposals have advocated a role for symbols and names as sensory representations (Harnad, 1990;Humphreys et al, 1999;Feldman and Narayanan, 2004;Sheridan, 2005).…”
Section: Introductionmentioning
confidence: 99%